Measuring The Performance Of State-Owned Assets Through The Asset Management Index - Octarina Yuhani; Dyah Setyaningrum (Publikasi Indonesia, 2023)
This study aims to analyze how the implementation of the Asset Management Index in Ministries / Institutions (M/I) and the problems that occur in the flow or process of implementing it. This research uses the theoretical framework of governance, risk, and compliance. This research uses a qualitative approach in the form of a case study conducted at the Directorate General of State Assets Management (DGSAM) as the unit authorized to formulate policies in the field of BMN management. Data collection was carried out through document review and in-depth interviews. The results of this study illustrate that there are obstacles in the application of the Asset Management Index in BMN Management including the use of state-owned asset management information systems and parameters in the calculation of IPA (tools), the application of standard operating procedures (process) and limited human resources (people).